Effectiveness of Multisensory-Based Statistical E-Comic with Collaborative Learning to Enhance Deaf Students’ Mathematical Connection - Sugiman; Najma Fatikasari; Emi Pujiastuti; Muh. Fajar Safaatullah; Endang Sugiharti (Hipotenusa: Journal of Mathematical Society, 2026)
Deaf students face challenges in understanding abstract mathematical concepts, especially the material of data concentration measures, due to limited verbal communication and lack of learning media that suits their characteristics. This study aims to examine the effectiveness of statistical e-comic based on multisensory approach integrated with collaborative learning model in improving mathematical connection ability of deaf students. The research approach used is mixed-methods with Single Subject Research (SSR) design type A-B-A. The subjects consisted of three deaf students of class VIII-B in SLB Negeri Ungaran who were purposively selected. Data collection techniques included mathematical connection tests, learning observations, semi-structured interviews, and visual documentation. Quantitative data was analysed using visual inspection charts within and between conditions, while qualitative data was analysed through reduction, presentation, interpretation, and conclusion drawing. The results showed that statistical e-comic media was effective in significantly improving deaf students' mathematical connections, both from cognitive (concept understanding), affective (motivation and attitude), and psychomotor aspects (digital skills and participation). The conclusion shows that statistical e-comic with multisensory approach and collaborative learning is able to bridge the gap of mathematical understanding contextually and applicatively.